Application of real option in risk evaluation and management of PPP/PFI projects - Liu, Jicai (2008)
The global movement away from heavy dependence on public sector financing, and toward greater reliance on private capital and control, means that the project finance mechanism will constitute an important tool to finance the large-scale infrastructure and industrial projects needed to support their economic development. A privately financed infrastructure project is inherently risky. Risk management in a project becomes a critical issue to both public sectors and private sectors. Risks mean losses to a project in the traditional risk management sense, and when the values of flexible measures to counteract such risks are overlooked, the value of a project may be understated. As an alternative approach, real option assumes that managers can take advantage of upsides and avoid obvious pitfalls during the development of a project. Such actions thus enhance the value of a project, and these are not captured in conventional evaluation methods such as Net Present Value. In this research, the primary objective is to study how real option can be applied to infrastructure projects with risks and uncertainties. The research aims to identify typical options in a project and evaluate them, design a new risk management framework incorporating the real option concept, which will lead to fairer risk allocation in a PPP/PFI setting.